FAKTOR YANG MEMPENGARUHI JUMLAH KEPEMILIKAN TERNAK SAPI POTONG DI KECAMATAN SUKARAJA KABUPATEN SELUMA - Nopita, Nopita; Kurniati, Novitri; Feni, Rita (Universitas Tribhuwana Tunggadewi, 2024)
This research aimed to determine the factors influencing the number of livestock ownership in beef cattle in Sukaraja District, Seluma Regency. The variables used in this research are the breeder's age, experience, calf price, income from the beef cattle business, rearing system, and type of cow. The research uses a survey method with field observation techniques and direct interviews with respondents. This type of research is quantitative descriptive. The sampling procedure utilized a proportional random sample. The samples taken were farmers engaged in beef cattle farming in the Sukaraja sub-district, 98 samples were used purposively using the Slovin formula. The data analysis technique uses Multiple Linear Regression analysis. The research results show that the average ownership of cattle kept by farmers is 3-5 head per farmer using intensive and semi-intensive rearing systems. The variables of calf price and income from the beef cattle business have a real impact. The breeder's age and experience have an impact on the number of beef cattle holdings. Meanwhile, the rearing system and type of cow have no significant effect on the number of beef cattle ownership.